A) 34 - ( 2⁵ ÷8) ×5
B) 26 + ( 42 ÷3) ×4 + 3 elevado a zero
C) 6³ - [ 2+ (4²-3) × 5]
Soluções para a tarefa
Respondido por
0
Explicação passo-a-passo:
Ordem para resolver as expressões:
1º potenciação
2° x ou :
3° + ou -
Resolução:
a) 34 - (2^5 : 8) x5 2^5= 2.2.2.2.2=32
34 - ( 32 : 8) x 5
34 - 4 x 5
34 - 20 = 14
b) 26 + (42 : 3) x 4 + 3^0 3^0= 1 ( qq n° elevado a zero é igual a 1)
26 + (14) x 4 + 1
26 + 56 +1= 83
c)6^3 - { 2+ (4^2 - 3) x 5} 6^3= 6.6.6= 216 4^2= 4.4= 16
216 - [ 2 + (16 -3) x 5]
216 - [ 2 + 13 x 5]
216 - [ 2 + 65]
216 - 67 = 149
Perguntas interessantes